2022
DOI: 10.3390/vaccines10050755
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough COVID-19 Infections in the US: Implications for Prolonging the Pandemic

Abstract: The incidence of COVID-19 breakthrough infections—an infection that occurs after you have been vaccinated—has increased in frequency since the Delta and now Omicron variants of the SARS-CoV-2 coronavirus have become the dominant strains transmitted in the United States (US). Evidence suggests that individuals with breakthrough infections, though rare and expected, may readily transmit COVID-19 to unvaccinated populations, posing a continuing threat to the unvaccinated. Here, we examine factors contributing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Besides, a previous study revealed that clinical symptoms of the SARS-CoV-2 infection among partially or fully vaccinated cases was significantly lower (odds ratio = 0.26 [95% CI: 0.07-0.94]) than in unvaccinated cases [36]. Dysregulation of immune function like inflammaging and immunosenescence can increase the vulnerability of subjects to COVID-19 and result in inefficient protection after vaccination [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a previous study revealed that clinical symptoms of the SARS-CoV-2 infection among partially or fully vaccinated cases was significantly lower (odds ratio = 0.26 [95% CI: 0.07-0.94]) than in unvaccinated cases [36]. Dysregulation of immune function like inflammaging and immunosenescence can increase the vulnerability of subjects to COVID-19 and result in inefficient protection after vaccination [37].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of immune function like inflammaging and immunosenescence can increase the vulnerability of subjects to COVID-19 and result in inefficient protection after vaccination [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, vaccination rates in recruited Paxlovid-treated patients and controls were much lower (20% in cases vs. 27% in controls) than in the whole population (6-14 years, >90%). In addition, with the prevalence of the SARS-CoV-2 Omicron variant, vaccine breakthrough infection has become more common (11), and it has been well studied that patients with underlying diseases are at risk of severe COVID-19, even after vaccination (12,13). In addition, in immunocompromised patients, SARS-CoV-2 may persist and cause subsequent resurgence or repositivity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“… 113 Although influenza and SARS-CoV-2 vaccines reduce disease severity when vaccines fail to prevent infection, significant numbers of fatalities still occur, resulting in tens of thousands of annual influenza deaths in the United States. 114 , 115 , 116 With the imperfections of these vaccines, it seems a public health imperative to aggressively pursue better vaccines and vaccination strategies.…”
Section: Immune Correlates Of Protection Against Mucosal Respiratory ...mentioning
confidence: 99%